2009
DOI: 10.5485/tmcs.2009.0212
|View full text |Cite
|
Sign up to set email alerts
|

Teaching word processing - the theory behind

Abstract: It is widely thought and believed that word processors-especially MS Wordare software, which everyone can use. However, if we take a closer look at the documents we find that the picture is not at all that clear. In most of these documents even the basic rules of word processing are broken. The question is how it is possible that most of the users are satisfied with their performance, and do not realize that they only use a less noisy typewriter, and not able to take advantage of the opportunities offered by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 1 publication
0
28
0
3
Order By: Relevance
“…Research found that those involved in end-user computing-central corporate IT groups, general corporate management, information systems researchers [1] [2] [9] [10], education policy-makers, teachers, publishers, and end-users [3] [4] [5] [11]-seem to be blind to effective teaching methods, to error handling, recognition, and correction, to how the brain works, how it can be utilized effectively in digital environments. Even those methods are not adopted which have proved effective in real world problem solving in other sciences and in programming.…”
Section: The State Of Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Research found that those involved in end-user computing-central corporate IT groups, general corporate management, information systems researchers [1] [2] [9] [10], education policy-makers, teachers, publishers, and end-users [3] [4] [5] [11]-seem to be blind to effective teaching methods, to error handling, recognition, and correction, to how the brain works, how it can be utilized effectively in digital environments. Even those methods are not adopted which have proved effective in real world problem solving in other sciences and in programming.…”
Section: The State Of Artmentioning
confidence: 99%
“…In the present paper, we argue that (1) end-user computing should not differ in nature from any other problem solving, (2) effective teaching methods and approaches can be adapted from other sciences (3) novel methods can and have to be invented and introduced, (4) what teachers do matters, and (5) what "some" teachers, the expert teachers, do matters [13] [14].…”
Section: Time For Changesmentioning
confidence: 99%
“…In an ideal educational environment, the development of computational thinking is not only focused on the programming topic, but rather integrated into all topics of ICT (Information and Communication Technology) education, such as Sprego and ERM (Spreadsheet Lego and Error Recognition Model), respectively [9], [10], [11], [12], [13], [14], [15]. Teaching birotical software receives great emphasis in the Hungarian K-12 curriculum [8], but most educators miss the opportunity to develop students' algorithmic skills by using such software [16].…”
Section: Developing Computational Thinkingmentioning
confidence: 99%
“…Others, that they can use word processors properly, has not yet been proved. To prove that their knowledge is satisfactory, that is, their texts created with word processors are correctly formatted, first the criteria of the properly formatted text had to be set ( [7]). According to this definition a text is properly formatted if the layout of the text is invariant to modification(s), in other words, any modification in the body of the text does not initiate its re-formatting.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing the texts of these two surveys, and other texts available on the Internet, I found that one of the reasons that we have not advanced much in the past ten years is that there is no clear understanding of the concept of the properly formatted text. As a result, a definition of the properly formatted text was published in 2009 ( [7]), in hope that this definition would clear up the mist on what is acceptable in word processing and what is not.…”
Section: Introductionmentioning
confidence: 99%